ANALYSIS OF TOURISM DESTINATION COMPONENTS OF ZARIA URBAN AREA OF KADUNA STATE, NIGERIA: TOURISM (FUDMA JOURNAL OF SCIENCES, 2020)
Tourism is not just a lucrative sector but the fastest growing industry in the world. Many people travel miles to satisfy their pleasure apatite at any destination where satisfaction can be met. But some destinations are flooded while some are scanty. There are many approaches to investigate this and many studies had been done. But despite all these, each destination is unique in terms of its components and attractions combination, this form the basis for this study. The aim of this study is to analyze tourism destination components in Zaria Kaduna State of Nigeria. Tourists’ opinions were sampled through questionnaire at various strategic centers to cover all tourism elements at the destination. Data collected were analyzed using Importance Performance Analysis technique (IPA). The results prove attraction to be the primary destination component i.e. main attractant, while accommodation and accessibility as secondary attractants (Facilitators) in the destination. The outcomes suggest major shortcomings that are traced to poor advertisement, insecurity in the destination e.t.c. The study established the state of the attractiveness of Zaria as a tourist destination, what components and elements are attractive and are not and the factors that influence these. In line with these, the study proposes recommendation that the local tourism board needs to be rejuvenated in other to enhance the local tourism industries to improve its attractiveness among others.
Keywords: Tourism Destination, Component (attraction accessibility, accommodation), Tourist.